Pemanfaatan Ruang Publik Pada Kawasan Rumah Toko di Kecamatan Panakkukang Makassar - Arsyad, Nashrah (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
Public spaces in urban areas play a significant role in the growth and development of cities. Their existence is an inseparable part of the buildings in urban environments. As a medium that connects and links various functions of urban areas, public spaces are widely utilized by communities for economic activities, social interactions, or simply for light recreation. However, the planning and design of public spaces have not received serious attention to adequately accommodate urban community activities. Economic growth has spurred the development of shophouses in several cities, including Makassar, in response to housing needs and economic demands. The development of shophouse areas should be balanced with the provision of facilities and infrastructure according to their demands and needs. However, in its development, the construction of shophouses has become uncontrolled due to economic pressures. Considering their function, shophouses, abbreviated as "ruko," aligned with the increasing commercial value of the area, place more emphasis on economic aspects while neglecting harmony with the surrounding environment. This study aims to examine the utilization of public spaces in the Shophouse Area of Panakkukang District, Makassar, through the identification of the existing conditions of public spaces, analysis of public space utilization based on the form, type, and function of public open spaces, as well as the patterns of public open space utilization within the Shophouse Area in Panakkukang District, Makassar. The entire analysis process in this study employs a descriptive qualitative approach using data collection techniques through document review, direct field observation, and interviews. The results of this study indicate that the utilization of public spaces in the Shophouse Area of Panakkukang is quite varied, although the provision of public spaces in the area is not accompanied by more optimal, proportional, and systemic planning and design.